Composition and Technology of Processing used Vehicle Tires and Obtaining Road Surfaces Base (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This scientific article proposes the technology of recycling tires and obtaining an environmentally safe finished product. Modern methods of preparation of the product composition are explained using scientific principles. In this invention, the scientific significance and foreign experiences of obtaining a finished product from secondary tire scraps and the development of new composite road plates were studied, and the mechanisms of waste utilization were studied. Technological processes, new methods, ingredients are studied in the article.